Comparative Analysis of Nkx2.1 and Islet-1 Expression in Urodele Amphibians and Lungfishes Highlights the Pattern of Forebrain Organization in Early Tetrapods - Nerea Moreno; Jesús M. López; Ruth Morona; Daniel Lozano; Sara Jiménez; Agustín González (Frontiers Media S.A., 2018)
Expression patterns of Nkx2.1 and Islet-1 (Isl1), which encode transcription factors that are key in the regionalization of the forebrain, were analyzed by combined immunohistochemical methods in young adult specimens of two lungfishes (Neoceratodus forsteri and Protopterus dolloi) and a urodele amphibian (Pleurodeles waltl). We aimed to get insights into the possible organization of the forebrain in the common ancestor of all tetrapods because of the pivotal phylogenetic significance of these two groups, being lungfishes the closest living relatives of tetrapods, and representing urodeles a model of simple brain organization with most shared features with amniotes. These transcription factors display regionally restricted expression domains in adult (juvenile) brains that are best interpreted according to the current prosomeric model. The regional patterns observed serve to identify regions and compare between the three species studied, and with previous data reported mainly for amniotes. We corroborate that Nkx2.1 and Isl1 expressions have very similar topologies in the forebrain. Common features in all sarcopterygians (lungfishes and tetrapods) have been observed, such as the Isl1 expression in most striatal neurons, whereas Nkx2.1 is restricted to migrated interneurons that reach the ventral pallium (VP). In the pallidal derivatives, the combination of both markers allows the identification of the boundaries between the ventral septum, the bed nucleus of the stria terminalis (BST) and the preoptic commissural region. In addition, the high Isl1 expression in the central amygdala (CeA), its boundary with the lateral amygdala (LA), and the scattered Nkx2.1 expression in the medial amygdala (MeA) are also shared features. The alar and basal hypothalamic territories, and the prethalamus and posterior tubercle (TP) in the diencephalon, have maintained a common pattern of expression. This regional distribution of Isl1 and Nkx2.1 observed in the forebrain of urodeles and lungfishes contributes further to our understanding of the first terrestrial vertebrates and their ancestors.